Sex work on Av. Alfonso Ugarte: urban materiality, place and body - Bravo, Mariana (2023)
The article examines the relationship between sex work and different urban experiences in a crowded area of downtown Lima. This is an abridged and adapted version of a research report prepared for the Urban Anthropology course at the Pontificia Universidad Católica del Perú. Based on the information gathered from urban methodology such as “floating observation” and secondarily from unstructured interviews, it seeks to describe and analyze the role of sex workers in the urban scenario of Alfonso Ugarte Avenue. The main hypothesis suggests that sex workers are protagonists of this space, since their presence determines and alters behaviors and beliefs of different actors. To this end, two main findings are presented: starting from the concept of “non-place” to understand the trajectories that sex workers and other agents establish in the area, in a sort of implicitly agreed urban choreography. Finally, we analyze the performative actions that sex workers perform with their bodies and the production of a series of symbols and meanings in relation to public space. We conclude by justifying that the presence of sex workers determines a series of social relations and performative actions in the area.